Leadership and Management Style: How to Choose an Effective Strategy - Kenjebaeva, Kamila (MMIT Proceedings, 2025)
The article examines the relationship between leadership and management styles, as well as the factors influencing the choice of an effective management strategy. An analysis of the main scientific approaches to the classification of management styles and their application depending on the situation is presented. The article also outlines the advantages and disadvantages of each style and provides examples of their practical implementation.